Karakteristik Wanita Pekerja Seks (WPS) dalam Melakukan Pemeriksaan HIV di Lokasi X, Y Kota Ternate Tahun 2022 - Tutik Lestari; Ridwan Yamko; Mudini Muhlis; Nurnaningsih Nurnaningsih; Febriyanti Febriyanti (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2023)
HIV AIDS in Ternate City are second ranks after North Halmahera District, especially in North Maluku Province. There were 684 HIV AIDS cases in 2007-April 2022, 24 new cases in 2022 (12 homosexuals, 10 heterosexuals and 2 IDUs). Early detection of HIV testing is one way of knowing HIV status, especially in people at high risk. The aim is to describe the characteristics of Sex worker in entertainment locations X and Y in their willingness to carry out an HIV test. The study was conducted in July 2022 with a total population of 50 sex worker at entertainment locations X and Y. Samples were taken by total sampling. Data were taken using the IBBS questionnaire and analyzed descriptively. Almost half of the respondents' age group is 30-39 years old (42%), high school education respondents (82%), unmarried respondents (66%) and respondents who have worked in entertainment venues X and Y for 1-5 years (60% ). More than half of the respondents had good knowledge (76%), all respondents received support related to HIV testing from peers, pimps and health workers as well as the role of health workers who always carried out HIV tests. The better the understanding and knowledge of HIV AIDS, the more motivated they are to be willing to take an HIV test because understanding the condition is a high risk. Keywords: Sex worker, HIV AIDS, HIV Test, Entertainment area